2014
DOI: 10.1039/c4cp01039f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermoelectric efficiency in ferromagnetic silicene nanoribbons terminated with hydrogen atoms

Abstract: Using ab initio methods we calculate thermoelectric and spin thermoelectric properties of silicene nanoribbons with bare, mono-hydrogenated and di-hydrogenated edges. Asymmetric structures, in which one edge is either bare or di-hydrogenated while the other edge is mono-hydrogenated (0H-1H and 2H-1H nanoribbons), have a ferromagnetic ground state and display remarkable conventional and spin thermoelectric properties. Strong enhancement of the thermoelectric efficiency, both conventional and spin ones, results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…Then, the Seebeck coefficient (thermopower) S c and spin Seebeck coefficient (spin thermopower) S s are given by the formulas [5,23] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the Seebeck coefficient (thermopower) S c and spin Seebeck coefficient (spin thermopower) S s are given by the formulas [5,23] …”
Section: Methodsmentioning
confidence: 99%
“…For instance, theoretical calculations show that considerable conventional and spin thermopowers can occur in zGNRs with antidotes [21] or in chemically functionalized zSiNRs [22,23]. In this paper we consider the influence of magnetic Co adatoms on transport properties, and especially on spin related thermoelectric phenomena in zSiNRs.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that a considerable spin S s and conventional S c thermopowers can be observed in ferromagnetic nanoribbons 15 . The effect can be further enhanced by structural defects like antidots 14 , impurity atoms 25 , or asymmetric hydrogenation of the edge atoms 26 . As a result, the thermoelectric efficiency of such systems can be enhanced in comparison to that in other materials, which makes these structures attractive for applications.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, thermoelectric properties of nanoribbons have been studied theoretically in a couple of papers. [38][39][40][41][42] However, the role of Coulomb interaction and topological edge states in the gap, has not been studied thoroughly enough yet. In a recent paper 43 we have analyzed the influence of topological states on the thermoelectric properties, with the main focus on the role of a staggered exchange field [5][6][7] and of an electric field perpendicular to the atomic plane.…”
Section: Introductionmentioning
confidence: 99%